Association Between Obesity and Post-stroke Anxiety in Patients With Acute Ischemic Stroke - Zhu, Bei-Lei; Hu, Ai-Yi; Huang, Gui-Qian; Qiu, Hui-Hua; Hong, Xian-Chai; Hu, Ping-Lang; Yuan, Cheng-Xiang; Ruan, Yi-Ting; Yang, Bo; He, Jin-Cai (Frontiers in Nutrition, 2021)
Post-stroke anxiety (PSA) is serious psychosomatic comorbidity among patients with stroke, but whether obesity could be positively associated with PSA is currently unknown. The purpose of this study was to investigate the potential association between obesity and subsequent anxiety risk in patients with stroke. A total of 441 patients with acute ischemic stroke (AIS) onset were consecutively recruited within 7 days, and PSA and post-stroke depression (PSD) were evaluated by using a 14-item Hamilton anxiety scale (HAMA) and 17-item Hamilton depression scale (HAMD) at the end of 1-month follow-up. The odds ratio (OR) with 95% CI was estimated for the incidental PSA by using logistic regression analysis. The incidence of PSA was 25.85% at the end of 1-month follow-up, with a significant difference between patients with and without abdominal obesity. Relative fat mass (RFM) and abdominal obesity were significantly associated with an elevated risk of PSA, and the crude ORs were 1.04 (95% CI: 1.01–1.08) and 1.93 (95% CI: 1.11–3.34), respectively. Even after adjustment for obesity-related risk factors and PSA-related clinical measurements, the association remained to be pronounced with abdominal obesity. However, RFM (OR = 1.03, 95% CI: 0.99–1.06, P = 0.053) and abdominal obesity (OR = 1.31, 95% CI: 0.80–2.15, P = 0.280) were not significantly associated with an elevated risk of PSD. Abdominal obesity was independently associated with the PSA instead of PSD, which may help predict PSA risk in clinical practice. Further prospective clinical studies with a long follow-up duration are warranted to verify this finding.